Parametric characterization of a mesomechanic kinematic caused by ondulation in fabric reinforced composites: analytical and numerical investigations - Marco Romano; Ingo Ehrlich; Norbert Gebbeken (Fracture and Structural Integrity)
A parametric characterization of a mesomechanic kinematic caused by ondulation in fabric reinforced composites is investigated by analytical and numerical investigations. Due to the definition of plain representative sequences of balanced plain-weave fabric reinforced single layers based on sines the variable geometric parameters are the amplitude and the length of the ondulation. The mesomechanic kinematic can be observed in both the analytic model and the FE-analyses. The analytic model yields hyperbolic correlations due to the strongly simplifying presumptions that neglect elasticity. In contrast the FE-analyses yield linear correlations in much smaller amounts due to the consideration of elastic parts, yet distinctly.